Social Movement Rhetoric: A Dialogue of Different Perspectives - Mat Nayan, Shahreen (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2011)
The study of social movements in communication has been influenced by both the humanities and the social sciences. Scholars following the functional and/or Burkean perspective offer different lens for understanding movements. However, neither is superior than the other since both perspectives has its own advantages and limitations. This essay seeks to deliberate three main concerns, mainly 1) How have communication scholars treated the rhetoric of social movements? 2) What are the major debates that have shaped the study of Social Movement Rhetoric? and 3) What are the major lapses and/or strengths of social movement rhetoric scholarship, particularly relative to social change outside of the US/West? While this paper is not an exhaustive description of all social-movements-related issues, it does however aim to serve as an initial guide for those who wish to understand the nature of social movements from a social science and humanistic lens. Ultimately, this paper also seeks to consider the differing perspectives as a source of dialogue for scholars of social movements.